Comparison of the physical profile of male and female athletes of obstacle races - Baptista, J.; Brandão, A.; Frontini, R.; Pereira, J.; Clemente, JM. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
With the constant increase of the female population in obstacle races in sport it is important to consider possible comparisons with men in terms of physical capacities. Thus, the present study aims to compare the morphological and functional characteristics between male (n = 27) and female (n = 6) of obstacle course running (OCR). The results show that, comparing the runners of both sexes, men have a BMI (t = 0.135, d = 0.692) and body mass (t = 0.001, d = 1.905) slightly higher, with women having more fat mass t = 0.001, d = 2,541). In terms of functional aspects, male practitioners obtained significantly higher values ​​of MRI in the back squat (t = 0.019; d = 1,120), pull-up (t = 0.001; d = 2,019) and throwing of the medicine ball (t = 0.001; d) = 3,469) compared to women. Concluding that in general men are more resistant, powerful, fast and agile, but with higher fatigue rates compared to women.